Her last whisper [large type] : a novel - Robards, Karen (Robards, Karen. Charlotte Stone novel., 2014)
Madness and murder invaded Dr. Charlotte Stone's life when she was just a girl, and made her a woman determined to save others from the horror she survived. An expert in the psychology of serial killers, Charlie can also communicate with the spirits of those who die violently. She has helped the FBI bring lethal predators to justice. Now she's ready to stop before her luck runs out. Too bad Charlie is too dedicated for her own good.